Design and Implementation Mobile Based Parking System - Mushollin, Muhammad Abdul; Susilo, Andi; Ulansari, Ramadhani (LPPM of STIMIK ESQ, 2018)
In the parking system the problem that often arises is the lack of information about the identity of motorists who enter and exit the parking area as well as the availability of parking spaces that are still empty so that motorists must surround the parking area, to overcome this problem, an application is designed and implemented to facilitate area information parking as well as ordering an Android-based platform. This study chooses Prototyping-Based Methodology as a part of Rapid Application Development (RAD)-Based Methodologies. Applications are built using Raspberry Pi3 and Ultrasonic Sensors as the main components. The final result is an application that has a parking message feature so that the allocation of parking spaces is done easily and quickly via a smartphone with the Android Platform.